Single-rooted primary first mandibular molar - Haridoss, SelvaKumar (BMJ Publishing Group, 2014)
Morphological variations like single-rooted molar in primary dentition are scarce. Understanding the root canal anatomy and variations is necessary for successful root canal therapy. The purpose of the present article is to report successful endodontic treatment of primary left mandibular first molar with an abnormal morphology of a single root. This case report highlights the importance of knowledge and its applications in the management of anomalous anatomic variants which play a crucial role in the success of endodontic treatment.